PENGARUH MEDIA PEMBELAJARAN POP UP TERHADAP HASIL BELAJAR MATERI IPS KELAS V SD NEGERI 12 KAYUAGUNG - Riski Rahmawati; Eni Heldayani; Jayanti Jayanti (Universitas Negeri Medan, 2022)
Abstrack : Pengaruh Media Pembelajaran Pop Up Terhadap Hasil Belajar Materi IPS Kelas V SDN 12 Kayuagung The Purpose of this study aims to determine whether there is an effect of pop-up learning media on the learning outcomes of class V social studies at SD Negeri 12 Kayuagung. The population is 42 students of class V. With a sample of 30 randomly selected, namely class V.A and class V.B. The method in this study is a quantitative experimental design, namely a true experimental design with a test only posttest design. Hypothesis testing using t-test Independent sample t-test. After doing the posttest test for social studies material, the experimental class got a score percentage of 73% and the control class got a score of 20%. The control class and the experimental class had a 53% increase in value. through t-test Independent sample t-test obtained sig (2-tailed) results, namely 0.000 ≤ 0.025 significant value. So it can be concluded that the results of learning using Pop Up media can affect the learning outcomes of fifth grade students, especially in social studies learning materials.